Quantitative biodistribution of biotherapeutics at whole body, organ and cellular levels by autoradiography. (10th September 2018) - Wang, Mengmeng; Zhan, Yutian; O'Neil, Shawn P; Harris, Stephen; Henson, Claire; McEwen, Andrew; Webster, Rob; O'Hara, Denise M
Aim: Tools for mapping and quantifying monoclonal antibody (mAb) and peptide biotherapeutics distribumtion were evaluated by comparing data from three independent methods conducted at the whole body, organ or tissue, and cellular levels.Materials & methods: [ 3 H]-mAb1 and [ 3 H]-peptide A were administered intravenously to rats followed by quantitative whole-body autoradiography, kidney macro-autoradiography and micro-autoradiography.Results: [ 3 H]-mAb1 and [ 3 H]-peptide A concentrations were measured in anatomical regions ranging from whole body to whole organ to sub-organ level, such as the kidney glomerulus, with increasing resolution. The tissue/blood [ 3 H]-mAb1 concentrations in selected kidney microenvironments were comparable among the three quantitative methods.Conclusion: Quantitative whole-body autoradiography, tissue macro-autoradiography and micro-autoradiography all provide useful tools for quantifying the concentrations of biotherapeutics at different anatomical levels in tissues, facilitating better predictions of efficacy and toxicity.